Step-by-step explanation:
4^5 (-2)^9/4^8 (-2)^3
= 4^(5 - 8) (-2^(9 - 3))
= 4^-3 (-2^6)
= (-2)^6/4^3
1). (-2)^a/4^b
a = 6, b = 3
2). c/d
c = -2, d = 4
The solution to the composite function f(g(x)) is 9x² - 78x + 165.
<h3>
What is composite function?</h3>
A composite function is generally a function that is written inside another function.
Function composition is an operation that takes two functions f and g, and produces a function h = g ∘ f such that h(x) = g.
From the given composite function, the solution is determined as follows;
to solve for f(g(x)), we use the following methods.
f(x) = x² + 2x - 3, g(x) = 3x - 14
f(g(x)) = (3x - 14)² + 2(3x - 14) - 3
= 9x² - 84x + 196 + 6x - 28 - 3
= 9x² - 78x + 165
Thus, the solution to the composite function f(g(x)) is 9x² - 78x + 165.
Learn more about composite function here: brainly.com/question/10687170
#SPJ1
The complete question is below:
F(x) =x2+2x-3 g(x)=3x-14, find f(g(x))
Answer:
d³y/dx³ = (-2xy² − 3x³ − 4xy²) / (8y⁵)
Step-by-step explanation:
d²y/dx² = (-2y² − x²) / (4y³)
Take the derivative (use quotient rule and chain rule):
d³y/dx³ = [ (4y³) (-4y dy/dx − 2x) − (-2y² − x²) (12y² dy/dx) ] / (4y³)²
d³y/dx³ = [ (-16y⁴ dy/dx − 8xy³ − (-24y⁴ dy/dx − 12x²y² dy/dx) ] / (16y⁶)
d³y/dx³ = (-16y⁴ dy/dx − 8xy³ + 24y⁴ dy/dx + 12x²y² dy/dx) / (16y⁶)
d³y/dx³ = ((8y⁴ + 12x²y²) dy/dx − 8xy³) / (16y⁶)
d³y/dx³ = ((2y² + 3x²) dy/dx − 2xy) / (4y⁴)
Substitute:
d³y/dx³ = ((2y² + 3x²) (-x / (2y)) − 2xy) / (4y⁴)
d³y/dx³ = ((2y² + 3x²) (-x) − 4xy²) / (8y⁵)
d³y/dx³ = (-2xy² − 3x³ − 4xy²) / (8y⁵)
The descent after 16 seconds would be 672 feet, with the function -42•X and X=16 so -42•16=-672
9514 1404 393
Answer:
- 0 ≤ m ≤ 7
- 0.4541 cm/month; average rate of growth over last 4 months of study
Step-by-step explanation:
<u>Part A</u>:
The study was concluded after 7 months. The fish cannot be expected to maintain exponential growth for any significant period beyond the observation period. A reasonable domain is ...
0 ≤ m ≤ 7
__
<u>Part B</u>:
The y-intercept is the value when m=0. It is the length of the fish at the start of the study.
__
<u>Part C</u>:
The average rate of change on the interval [3, 7] is given by ...
(f(7) -f(3))/(7 -3) = (4(1.08^7) -4(1.08^3))/4 = 1.08^3·(1.08^4 -1)
≈ 0.4541 cm/month
This is the average growth rate of the fish in cm per month over the period from 3 months to 7 months.